DESIGN OF A FIRE DETECTION SYSTEM USING FIRE AND SMOKE SENSORS BASED ON ARDUINO MICROCONTROLLER - Firdaus Firdaus; Yunus Tjandi; Adrian Pratama (Jurusan Pendidikan Teknik Elektro, 2024)
Fires very often occur due to gas leaks, careless throwing of cigarette butts or electrical short circuits which result in the fire getting bigger, causing a lot of losses. Many fire cases are discovered when the fire has already occurred and few can be detected from the start. The research aims to develop an effective system for detecting fires by integrating fire and smoke sensors, as well as providing notifications via the Blynk platform. This research is research and development (R&D) using a prototype development model. The results of the functionality testing obtained a 100% presentation which shows that the prototype is suitable for use. Tests were carried out using three levels of fire levels and various distances, showing good response from the fire sensor with a consistent incoming notification speed of around 2-3 seconds. The results of fire measurements using the MQ-2 smoke sensor show accuracy in detecting smoke concentration levels, with timely notification of potential fires. This research has produced a detection tool that has the ability to detect early fire in a room which can provide warning notifications that are integrated with Internet of Things (IoT).